Remote ischemic preconditioning enhances aerobic performance by accelerating regional oxygenation and improving cardiac function during acute hypobaric hypoxia exposure - Zhong, Zhifeng; Dong, Huaping; Wu, Yu; Zhou, Simin; Li, Hong; Huang, Pei; Tian, Huaijun; Li, Xiaoxu; Xiao, Heng; Yang, Tian; Xiong, Kun; Zhang, Gang; et al. (Frontiers in Physiology, 2022)
Remote ischemic preconditioning (RIPC) may improve exercise performance. However, the influence of RIPC on aerobic performance and underlying physiological mechanisms during hypobaric hypoxia (HH) exposure remains relatively uncertain. Here, we systematically evaluated the potential performance benefits and underlying mechanisms of RIPC during HH exposure. Seventy-nine healthy participants were randomly assigned to receive sham intervention or RIPC (4×5 min occlusion 180 mm Hg/reperfusion 0 mm Hg, bilaterally on the upper arms) for 8 consecutive days in phases 1 (24 participants) and phase 2 (55 participants). In the phases 1, we measured the change in maximal oxygen uptake capacity (VO2max) and muscle oxygenation (SmO2) on the leg during a graded exercise test. We also measured regional cerebral oxygenation (rSO2) on the forehead. These measures and physiological variables, such as cardiovascular hemodynamic parameters and heart rate variability index, were used to evaluate the intervention effect of RIPC on the changes in bodily functions caused by HH exposure. In the phase 2, plasma protein mass spectrometry was then performed after RIPC intervention, and the results were further evaluated using ELISA tests to assess possible mechanisms. The results suggested that RIPC intervention improved VO2max (11.29%) and accelerated both the maximum (18.13%) and minimum (53%) values of SmO2 and rSO2 (6.88%) compared to sham intervention in hypobaric hypoxia exposure. Cardiovascular hemodynamic parameters (SV, SVRI, PPV% and SpMet%) and the heart rate variability index (Mean RR, Mean HR, RMSSD, pNN50, Lfnu, Hfnu, SD1, SD2/SD1, ApEn, SampEn, DFA1and DFA2) were evaluated. Protein sequence analysis showed 42 unregulated and six downregulated proteins in the plasma of the RIPC group compared to the sham group after HH exposure. Three proteins, thymosin β4 (Tβ4), heat shock protein-70 (HSP70), and heat shock protein-90 (HSP90), were significantly altered in the plasma of the RIPC group before and after HH exposure. Our data demonstrated that in acute HH exposure, RIPC mitigates the decline in VO2max and regional oxygenation, as well as physiological variables, such as cardiovascular hemodynamic parameters and the heart rate variability index, by influencing plasma Tβ4, HSP70, and HSP90. These data suggest that RIPC may be beneficial for acute HH exposure.